Smart Apps Creator Warak Ngendhog with SAVI Learning Model to Enhance Critical Thinking and Poetry Comprehension - Safirra Wahyu Citera Purnama; Panca Dewi Purwati (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to design, assess the feasibility, and evaluate the effectiveness of Smart Apps Creator Warak Ngendhog as a digital learning medium to enhance critical thinking and poetry comprehension among Grade IV students at Elementary School Kalibanteng Kidul 01. Methodology: Insects The research employed a Research and Development (R&D) approach using the Borg & Gall development model, completed up to the eighth stage. Participants included 28 Grade IV students. Data collection involved feasibility assessments by experts, teacher and student response questionnaires, normality testing, t-tests, and N-Gain analysis. Main Findings: The Smart Apps Creator Warak Ngendhog media was successfully developed to address learning needs and promote both cognitive and literary skills. Feasibility ratings were highly positive, with scores of 96% from media experts and 90% from content experts. Statistical analysis confirmed its effectiveness, with t-test results showing Sig. (2-tailed) = 0.000 (< 0.05). Novelty/Originality of this study: This research introduces an innovative integration of local cultural heritage—Warak Ngendhog poetry—into a modern, interactive digital application developed with Smart Apps Creator. Unlike conventional poetry teaching methods, the media adopts the SAVI (Somatic, Auditory, Visual, Intellectual) learning model, tailored to students’ developmental levels, and incorporates HOTS (Higher Order Thinking Skills)-based evaluation questions. This dual emphasis on cultural literacy and 21st-century learning skills positions the media as both a preservation tool for local traditions and a catalyst for higher-order cognitive development.